Monumentos de CuencaMonuments of Cuenca
Contiene: Monumetos: Chola de Cuencana, Andrés Hurtado de Mendoza, Benigno MAlo, ElBarranco del Tomebamba, El Puente Roto,La Picota del Vecino, Carlos Cueva Tamariz, La Virgen de la Merdec, José Peralta,El PAdre Crespi, El Hermno Miguel, FRay Vicente Solano, Elia Liut, Julio Matovelle, Honorato Vazquez, Gabriela Mistral, Simón Bolívar,Luis Cordero, Remigio Crespo Toral